A12 INTESINAL TREFOIL FACTOR (ITF) PLAYS CRITICAL ROLES IN INNATE PROTECTION AGAINST, AND RECOVERY FROM, CLOSTRIDIUM DIFFICILE COLITIS. (1st March 2018) - Tang, H; Li, Y; Nguyen, J; MacDonald, J A; Gui, X; Beck, P
Abstract: Background: Clostridium Difficile (Cdif) colitis is a leading cause of morbidity & mortality in many patients including: hospitalized elderly, those with IBD, and immunocompromised. Little is known of the mechanisms involved in protection against, and recovery from, Cdif toxin-induced injury. Histological findings of Cdif colitis include; epithelial disruption, inflammatory cell infiltration, goblet cell depletion & when severe, pseudomembranous colitis (PMC). We previously showed Keratinocyte Growth Factor (KGF) plays protective roles on Cdif exposure. KGF-/- mice had more severe Cdif toxin-induced injury & greater depletion of goblet cells and the goblet cell derived growth factor ITF. Since KGF directly binds the ITF promoter (increasing ITF) and Cdif colitis is associated with goblet cell depletion & loss of ITF we developed the following aim. Aims: We hypothesized that ITF protects against Cdif induced injury and is critical in resolution of Cdif colitis. Methods: Cdif colitis was induced in Sv129 (WT) and ITF -/- mice via intrarectal (IR) Cdif toxin (TcdA/B). In vitro models of toxin exposure, IECs (CaCo2) and fresh human colonic biopsies, were also assessed. Cdif injury/inflammation was assessed via histology, myeloperoxidase activity (MPO), cytokine/chemokine profiles, lactate dehydrogenase (LDH) release & epithelial proliferation/apoptosis balance. Results: IR Cdif toxin resulted in marked depletion in goblet cells & ITF (4h post). Reductions in goblet cell numbers & ITF correlated with severity of injury/inflammation & increased during the resolution phase (24–72 h post). Goblet cell & ITF depletion was also seen in fresh human colon biopies exposed to Cdif toxin. Although ITF -/- mice had similar MPO levels & histological damage as WT mice at 4h post toxin exposure they had marked impairment in recovery from colitis (significantly higher MPO, cytokine/chemokine levels & histological scores at 48h and 72h after toxin exposure vs WT). Loss of ITF also resulted in increased epithelial apoptosis & impaired proliferation following Cdif toxin exposure. Loss of ITF also resulted in a close to 10 fold increased incidence in PMC (1 of 32 wt mice (3%) vs 6 of 24 ITF-/- mice (25%). IR recombinant ITF (rITF) protected WT mice from toxin-induced injury, enhanced recovery & reduced the incidence of PMC. In vitro studies showed that rITF decreased Cdif toxin induced cell death (LDH), promoted cell proliferation, enhanced wound repair & altered cell cycle dynamics (enhancing cell survival). Conclusions: In both humans & mice, Cdif toxin induces depletion of goblet cells and ITF. ITF plays important roles in the innate protection against Cdif colitis, and is critical in mucosal healing following Cdif colitis. These studies may lead to new approaches in the management and prevention of Cdif in patients. Funding Agencies: CIHR